Magnetohydrodymanic Natural Convection Flows Resulting From the Combined Buoyancy Effects of Thermal and Mass Diffusion - Samaan, A.A.; Ibrahim, F.N. (Engineering Transactions, 1994)
This paper presents a study of laminar doubly diffusive free convection flows of a viscoelastic fluid past an oscillating vertical plate in the presence of a transverse magnetic field. The two buoyant mechanisms are the thermal diffusion and species diffusion. The governing conservation equations of momentum, energy and concentration are nondimensionalized and solved analytically. Effects of Pr (Prandtl number), Sc (Schmidt number), Gr (Grashof number), Gm (modified Grashof number), M (magnetic number), ω (frequency parameter) and k (viscoelastic parameter) upon the velocity field, the shear stress on the plate, the temperature field and the concentration field are discussed. The results show many interesting aspects of the complex interaction of the two buoyant mechanisms.